Analisis Pengaruh Cultural Heritage, Responsiveness dan Communication terhadap Revisit Intention ke Destinasi Wisata Eks Kamp Pengungsi Vietnam di Batam dengan Tourist Satisfaction sebagai Variabel Mediasi - Kurniawan, Robby; Yessyana, Yessyana (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
Tourists always want to feel a unique experience, be it tourist attractions, culture and history in any country. That way, cultural tourism of an area can be an interest for tourists visiting the place. The purpose of this study is to determine the influence of cultural heritage, responsiveness, communication on tourist satisfaction on revisit intention which can help tourism business actors in designing and determining strategies to encourage consumer decisions to visit again. The target of this study is tourists who have visited tourist destinations of former Vietnamese refugee camps. To reach many respondents, the author uses a google form which is then disseminated using social media. The data obtained used 5 indicators that included demographics, value of cultural relics of the destination, response, communication, travel satisfaction and intention to visit again. The results of this study show that cultural heritage, responsiveness and communication have a significant effect on tourist satisfaction simultaneously but from the results of the T cultural heritage test shows that it does not have a significant effect on tourist satisfaction. Likewise, the effect of tourist satisfaction on revisit intention shows significant results. Overall, the discovery of these results can help tourist destinations of the Former Vietnamese Refugee Camp to design strategies and improve their quality so that they can develop into better known tourist destinations.